Global trends in throwing techniques and performance in women's shot put - Hatase, S.; Okada, T.; Takanashi, Y. (Scientific Journal of Sport and Performance, 2025)
The aim of this study was to investigate global trends in throwing techniques and performance in women`s shot put to provide useful data for future advancements. The study focused on the period from 2008 to 2024, analyzing records and trends of athletes placing in the top-eight at the World Championships and the Olympics. Additionally, the study examined characteristics of the top-eight finishers who adopted the rotational technique after its introduction to the sport in 2015. The primary source of data used for this analysis was World Athletics (https://worldathletics.org/). The results showed that there was no statistically significant change in the performance level for top-eight finishers in the World Championships and Olympics since 2008. Significant (p = .002) differences were observed between Group G (33.00 [28.50-34.50]) and Group R (27.00 [24.75-29.00]) in terms of their age. These findings suggest that the rotational throw technique has not yet contributed to improving performance at the competition level in women`s shot put. However, given the younger age of rotational throwers, further improvements in performance are expected in the future.